FAMILY LANGUAGE POLICY IN KAZAKHSTANI FAMILIES - Нұркентаева, М.; Абжанова, С.; Мұсабекова, С. ("МӘҢГІЛІК ЕЛДІҢ МӘҢГІЛІК ТІЛІ" Халықаралық симпозиум материалдары/ THE ETERNAL LANGUAGE OF THE ETERNAL NATION international symposium, 2016)
Kazakhstan is a dynamically developing young country where about 130 nations and nationalities live together in peace and harmony for about 25 years since Kazakhstan has gained its independence from the Soviet Union. Having population with about 17 million people, Kazakhstan is developing trilingual policy in the educational system and aim at increasing the number of speakers in the state official language (i.e. Kazakh) up to 100%, Russian and English up to 85% and 25% respectively by 2020. Мақалада Қазақстандағы үштілділік мәселесі қарастырылған. Тілдердің үштұғырлығы мәдени жобасының жоғары оқу орындарында, қоғамда жүзеге асырылу барысында қазақстандықтардың өміріне, білім беру саласына, сондай-ақ экономикаға тиімді әсері сипатталады.
Keywords: kazakh language; goal of Language Policy; dynamically developing; family language policy; білім беру саласы; экономика; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education